P1148THE ASSOCIATION WITH LOWER SYSTOLIC BLOOD PRESSURE AND ALL-CAUSE MORTALITY IN PATIENTS UNDERGOING PERITONEAL DIALYSIS. (6th June 2020) - Kurahashi, Motoyasu; Harada, Kenji; Kanai, Hidetoshi
Abstract: Background and Aims: Previous observational studies have been reported that a U-shaped association between systolic blood pressure (SBP) and mortality in patients undergoing hemodialysis. However, the optimal blood pressure in patients undergoing peritoneal dialysis (PD) remains unclear. Method: The present study is observational and conducted in a single center. Four hundred and sixteen patients undergoing PD managed in our hospital from April 2010 to December 2017 were participated in this study. The patients were divided into four groups depended on office SBPs, as follows; group1: SBP <110 mmHg (n=60), group2: SBP 110-139 mmHg (n=187), group3: SBP 140-159 mmHg (n=113) and group4: SBP ≧160 mmHg (n=56). When using the Cox proportional hazards model, group 2 was regarded as a reference. Hypertension was defined as SBP ≧140 mmHg, diastolic blood pressure ≧90 mmHg, or use of any anti-hypertensive drugs. The association between SBP with several outcomes such as the risk of all-cause deaths, cardiovascular events and these composite events were estimated using cox proportional hazards model. Adjusted factors were age, sex, comorbidities, laboratory covariates, left ventricle ejection fraction and medications such as renin-angiotensin system blockades and statins. Results: The mean follow-up period was 29.2 months. The prevalence of hypertension was 90.4% (n=376) of all patients. The risk of all-cause deaths with multivariate cox proportional hazards regression analysis was significantly higher in the group 1 (hazard ratio 2.08, 95% CI 1.23-3.51, p=0.006). While the risk of CV events with univariate analysis tended to be higher in group 4, there was no significant association between SBP and the risk of CV events with multivariate analysis. The risk of the composite events with multivariate analysis was significantly higher in group 4 (hazard ratio 1.61, 95% CI 1.01-2.57, p=0.047). Conclusion: This study indicated that lower SBP was independently associated with all-cause mortality in patients undergoing PD. Moreover, higher SBP might be involved with composite events.